2002
DOI: 10.1149/1.1430414
|View full text |Cite
|
Sign up to set email alerts
|

Selective Dissolution below the Critical Potential and Back Alloying in Copper-Gold Alloy

Abstract: Below the critical potential, E c , selective dissolution of Cu from Cu-18 atom % Au proceeds via Cu transport through an essentially planar Au-rich product layer, which over time increases to hundreds of atom layers in thickness. Transmission electron micrographs ͑TEM͒ taken after the selective dissolution ͑at E Ͻ E c ͒ and subsequent ͑current-off͒ back alloying processes reveal nearly uniform Moire ´patterns characteristic of the superposition of two layers with similar crystal structures, i.e., the Cu-deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
1
21
0
1
Order By: Relevance
“…1(b), are extremely rare, consistent with the established notion (see, e.g., Refs. [8,14]) that the crystal lattice orientation is retained during dealloying and with the conservation of the 50-100 m grain size of the master alloy. This grain structure remains visible in FIB images of NPG [ Fig.…”
mentioning
confidence: 99%
“…1(b), are extremely rare, consistent with the established notion (see, e.g., Refs. [8,14]) that the crystal lattice orientation is retained during dealloying and with the conservation of the 50-100 m grain size of the master alloy. This grain structure remains visible in FIB images of NPG [ Fig.…”
mentioning
confidence: 99%
“…The sample fractured after 661 h at a constant potential of 143 mV Based upon the half-reaction oxidation potentials, given in Table 5, of each element it is determined that the corrosion rate is controlled initially by the dissolution of Zn and the formation of ZnCl 2 . This is followed by the dissolution of copper, nickel, or palladium below E c (15). There is a gradual enrichment of the Cu, Ni, or Pd-depleted layer with Au producing a concomitant increase in the lattice parameter during dissolution.…”
Section: Figurementioning
confidence: 99%
“…The experiments showed that all three alloys suffered from IGSCC. Since all tests were done at the maximum corrosion rate, below E c , for the system the fracture morphology was primarily intergranular (15). Figure 6 shows an SEM image of the fracture surface of 18K yellow gold after failure in dead weight loading in caustic sodaLiquiChlor.…”
Section: Dead Weight Testsmentioning
confidence: 99%
“…In recent years research has concentrated on using dealloying as a means of producing high-surface-area substrates for catalysis and other purposes [3][4][5][6][7][8]. The subject of deliberate dealloying as a manufacturing process has been reviewed in the American Society for Metals (ASM) International Metals Handbook [9] and will not be discussed further in this chapter.…”
Section: B Historymentioning
confidence: 99%